Design universal na arquitetura de exposições museológicas: aspectos inclusivos sob a perspectiva do público - Paulo Roberto Sabino (2017)
This research deals with the use of Universal Design in the architecture of the exhibition space of museum in the perspective of accessibility and social inclusion. Its objective is to evaluate the access to projects of exhibitions design that result in a quality experience for all, considering their abilities and autonomy. The high number of people with disabilities and a projection that suggests the increase of the aging indices of the Brazilian population demand that the society organizes itself in the search for the practice of accessibility. Currently, the museum exhibitions in Brazil are predominantly excluding spaces. The lack of sensitivity and knowledge of the companies and managers of museums that act in the planning of expositions create barriers that generate humiliation and social exclusion. In order to offer possibilities for changing that picture, this study proposes an accomplishment of collection and analysis of data in exhibition spaces of Belo Horizonte city. A search, performed using a previously established parameter, sought to identify how to enter external elements into the quality of the visitor's experience. It consists of the observation of visitors using time and tracking methodology, with a questionnaire application. It also performed simulations using an empathic model. A review of the literature was produced in an interdisciplinary theoretical analysis from fields that guide and influence the design of exhibitions. As a result, this work presents a relation of practices with the principles of Universal Design and may contribute to a promotion of accessibility in museums and, consequently, to the development of an inclusive society